2012
DOI: 10.6017/ital.v31i2.2166
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technologies & Academics: Do Students Use Mobile Technologies in Their Academic Lives and are Librarians Ready to Meet this Challenge?

Abstract: In this paper we report on two surveys and offer an introductory plan that librarians may use to PURPOSE OF THE STUDYSimilar to colleagues in all types of libraries around the world, librarians at Utah State University (USU) want to take advantage of opportunities to provide information resources and library services via mobile devices. Observing growing popularity of mobile, Internetcapable telephones and computing devices, USU librarians assume that at least some users would welcome the ability to use such d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 10 publications
5
70
0
3
Order By: Relevance
“…In a study of 75 students enrolled in an introductory information literacy class, Bomhold (2013) found that 35 of 42 survey respondents used their mobile devices to find academic information (p. 429). This data corroborated the findings Dresselhaus and Shrode (2012) obtained during their 2011 survey inquiring about student use of mobile technology for academic purposes. The results of both studies indicated that the majority of students use mobile devices for academic objectives (Bomhold, 2013, p. 430;Dresselhaus & Shrode, 2012, p. 89).…”
Section: Search Queriessupporting
confidence: 80%
“…In a study of 75 students enrolled in an introductory information literacy class, Bomhold (2013) found that 35 of 42 survey respondents used their mobile devices to find academic information (p. 429). This data corroborated the findings Dresselhaus and Shrode (2012) obtained during their 2011 survey inquiring about student use of mobile technology for academic purposes. The results of both studies indicated that the majority of students use mobile devices for academic objectives (Bomhold, 2013, p. 430;Dresselhaus & Shrode, 2012, p. 89).…”
Section: Search Queriessupporting
confidence: 80%
“…However, some universities have established online services of the library as a respond to student interest. (Dresselhaus, Shrode, 2012). Researchers find out that the academic performance of higher education students cannot be tested by their GPA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some universities have shown some action toward the story and begun to work on online libraries. (Dresselhaus, Shrode, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of undergraduate users reported employing the devices for academic work, but the most common types of apps used were search engines, and apps for websites that the user was already familiar with from their full-sized devices (Bomhold, 2013). Dresselhaus and Shrode (2012) examined smartphone use by different types of students; fifty-four percent of undergraduates and 50% of graduates reported using mobile devices for academic work. The highest use by students (63%) was in the College of Business followed by 59% of engineering students (Dresselhaus & Shrode, 2012).…”
Section: User Behaviormentioning
confidence: 99%
“…Dresselhaus and Shrode (2012) examined smartphone use by different types of students; fifty-four percent of undergraduates and 50% of graduates reported using mobile devices for academic work. The highest use by students (63%) was in the College of Business followed by 59% of engineering students (Dresselhaus & Shrode, 2012). Art and design undergraduate students used their mobile devices no differently than their peers in other colleges, aside from image and audio-visual needs (Lo et al, 2016).…”
Section: User Behaviormentioning
confidence: 99%